Cochlostoma revised: the subgenus Clessiniella Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae) - Zallot, Enrico; De Mattia, Willy; Fehér, Zoltán; Gittenberger, Edmund (European Journal of Taxonomy, 2021)
Five species of the subgenus Clessiniella of Cochlostoma (Cochlostomatidae) are recognized, viz. Cochlostoma (Clessiniella) villae (Strobel, 1851), Cochlostoma (Clessiniella) tergestinum (Westerlund, 1878), Cochlostoma (Clessiniella) waldemari (A.J. Wagner, 1897), Cochlostoma (Clessiniella) anomphale Boeckel, 1939 and Cochlostoma (Clessiniella) stelucarum sp. nov. The shells and the genitalia are described and the distributional data are summarized for all the species.